Hydrogen type dendritic catalyst as well as preparation method and application thereof
By preparing hydrogen-type dendritic catalysts by ion exchange using dendritic silicon source support and aluminum source, the problems of insufficient catalyst activity and uneven product distribution in the prior art are solved, and efficient and stable α-olefin polymerization and PAO lubrication are achieved. Oil production reduces costs and improves the stability of the catalyst.
Patent Information
- Application Number
- CN202410861079.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-03
AI Technical Summary
The existing olefin polymerization catalysts have problems such as insufficient catalyst activity, difficulty in separation and recovery, high cost and uneven product distribution in high-carbon hydrocarbon polymerization, and the catalyst is often prone to short-term due to the weak binding force of the catalyst active components and the support. Inactivated.
Using dendritic silicon source as a support, doped into the aluminum source and prepared hydrogen-type dendritic catalysts through ion exchange to form a catalyst with a three-dimensional central radial channel and multi-stage pore structure, which is used to catalyze α-olefin polymerization and adjust the silicon-aluminum ratio. to control product distribution.
Highly efficient catalytic α-olefin polymerization is achieved, the product distribution is narrow, the catalyst has higher activity and stability, and the cost is low. It can adjust the performance of PAO lubricant by changing the silicon-aluminum ratio, and maintain good performance under high temperature and high pressure conditions.
Smart Images

Figure CN119236913A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyolefin catalysts and relates to a hydrogen-type dendritic catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of emerging industries such as aerospace and robotics and the continuous improvement of energy conservation and environmental protection requirements, the lubricant industry, as the flowing "blood", urgently needs to transform towards high quality and high-end. The increase in demand for high-end lubricant products and the acceleration of lubricant upgrading have led to the rapid growth of polyalphaolefin (PAO) synthetic lubricants with superior performance, and its market development potential is huge. The main properties of PAO, such as pour point, kinematic viscosity and viscosity index, are greatly affected by the microstructure of its oligomers. The structure of oligomers (including molecular weight and its distribution, branch type and ratio) mainly depends on the degree of polymerization and molecular weight distribution of the product, and the catalyst is the key factor in determining the degree of polymerization and molecular weight distribution.
[0003] The types of catalysts for synthesizing PAO mainly include Lewis acid type, Ziegler-Natta type, metallocene, ionic liquid, etc. Among them, Lewis acid catalysts are highly valued at home and abroad due to their high activity and good stability. Common Lewis acid catalysts include BF3 and AlCl3. However, the high content of halides in the homogeneous system has serious corrosion to the equipment, causing a series of environmental problems; and the catalyst cannot be separated and cannot be recycled, which not only produces waste liquid, but also affects the efficiency and benefits of the entire production process. In view of the above defects, heterogeneous catalysts prepared by immobilization have overcome the problems of difficult separation of products and catalysts, strong corrosion of catalysts and difficulty in recycling to a certain extent.
[0004] Patent JP2018087285 "Manufacturing olefin polymerization catalyst component for olefin polymerization catalyst used for manufacturing olefin polymer involves reacting organoaluminum compound, organoaluminumoxy compound and silica gel" discloses a catalyst composed of an organoaluminum compound (A), an organoaluminumoxy compound (B) with an alkyl and aluminum molar ratio of 1.55 to 1.75, and a silica gel (C) with an average particle size of 2 to 200 μm, wherein the molar ratio of aluminum in component (A) to aluminum in component (B) is 0.12 to 0.24. The catalyst can produce olefin polymers with high catalytic activity and high density. However, the catalyst is currently only used for the polymerization of low-carbon hydrocarbons, and high-carbon hydrocarbons have not yet been involved. Patent WO2023246009 "Catalyst composition useful in polymerization of olefin, preferably egethylene, propylene, 1-butene, 1-pentene, and 1-heptene, comprises main catalyst containing metallocene complex and carrier containing fluorinated silica gel particles" discloses a novel olefin polymerization catalyst composition, including a main catalyst and a carrier, wherein the carrier is fluorinated silica gel particles and the main catalyst is a metallocene complex. The composition can reduce or avoid the use of methylaluminoxane or borate reagents while improving the polymer morphology, and has the characteristics of high polymerization activity, adjustable isotacticity, high polymer bulk density and good morphology within one hour of polymerization time. However, the catalyst involves metallocene and is relatively expensive.
[0005] Domestically, patent CN110041457 "A polyolefin lubricant base oil and its preparation method" discloses an olefin polymerization catalyst, which is composed of an alkyl aluminum alcoholized carrier and an active component titanium compound. It has better PAO product performance and polymerization activity, but the yield is relatively low, and it needs the support of a co-catalyst, which further increases the reaction cost. CN111013611 "A method for preparing an olefin polymerization catalyst, a method for preparing a poly-α-olefin base oil" discloses a Cr-AlCl3 / Al2O3 catalyst with γ-Al2O3 as a carrier, chromium metals and aluminum trichloride as active ingredients. The catalyst has high activity in catalyzing the polymerization reaction of α-olefins, and the chlorine content in the product is low, which avoids the corrosion of the reactor by the homogeneous catalyst. However, its product distribution is too wide and difficult to control. Patent CN114797821 "Decene oligomerization catalyst for lubricating oil and its preparation method and application" discloses a Lewis acid nanoparticle catalyst with a silicon source as a carrier and an aluminum source providing acid sites. The silicon source is silicon oxide, and the aluminum source is aluminum oxide, and the two are immobilized together by a solvent, a surfactant and a pH regulator. The catalyst particles are complete in shape, well dispersed, and have excellent catalytic activity. After four reaction cycles, the catalytic performance remains unchanged. However, the application conditions of the catalyst are relatively harsh, especially in terms of material ratio, which increases the application cost.
[0006] At present, there are many studies on immobilized catalysts for olefin polymerization, but the catalysts are easily deactivated in a short period of time due to the weak binding force between the active components of the catalyst and the carrier, pore blockage, etc. There is no immobilized catalyst system that has both high catalytic activity and good stability. Summary of the invention
[0007] The purpose of the present invention is to provide a hydrogen-type dendritic catalyst and its preparation method and application. The catalyst is prepared by using a dendritic silicon source as a carrier, adding an aluminum source and further ion exchange. Compared with other catalysts, the hydrogen-type dendritic catalyst has three-dimensional central radial channels and a multi-level pore structure, and has the advantages of higher specific surface area, larger pore volume, and easier contact of the inner surface of the particles. The hydrogen-type dendritic catalyst can be used to catalyze the polymerization of α-olefins to prepare poly α-olefin (PAO) lubricating oil base oil, and the distribution of the polymerization product is narrow. In addition, the composition of the polymerization product can also be adjusted by changing the silicon-aluminum ratio in the catalyst.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] The first aspect of the present invention provides a method for preparing a hydrogen-type dendritic catalyst, comprising the following steps:
[0010] S1: heating and stirring the alkali source, surfactant and structure regulator, and then adding the silicon source for secondary heating and stirring, cooling to obtain a milky white slurry, drying and calcining to obtain a dendritic silicon source carrier;
[0011] S2: mixing the dendritic silicon source carrier and the aluminum source, impregnating, drying and calcining to obtain a dendritic catalyst;
[0012] S3: exchanging the dendritic catalyst with ammonia ions and calcining the catalyst to obtain a hydrogen-type dendritic catalyst.
[0013] The catalyst prepared by the invention has a dendritic structure, a particle size of 250-300nm, and has weak acid and medium-strong acid active sites. It is prepared by using a dendritic silicon source as a carrier, doping an aluminum source, and performing ion exchange. It can be used to efficiently catalyze the polymerization of alpha-olefins to prepare polyalpha-olefins (PAO).
[0014] Furthermore, in step S1, the alkali source is selected from one or more of triethanolamine, ethylenediamine or ammonium hydroxide. Preferably, the alkali source is triethanolamine.
[0015] Furthermore, in step S1, the surfactant is selected from one or more of hexadecyltrimethylammonium chloride, hexadecyldimethylammonium chloride or hexadecyltrimethylammonium bromide. Preferably, the surfactant is hexadecyltrimethylammonium bromide.
[0016] Furthermore, in step S1, the structure regulator is selected from one or more of sodium salicylate, sodium laurate or sodium dodecyl sulfate. Preferably, the structure regulator is sodium salicylate.
[0017] Furthermore, in step S1, the silicon source is selected from one or more of sodium silicate, tetramethyl orthosilicate, tetraethyl orthosilicate or silica sol. Preferably, the silicon source is tetraethyl orthosilicate.
[0018] Furthermore, in step S1, the mass ratio of the alkali source, surfactant, structure regulator and silicon source is (3-5):(20-24):(9-12):(220-225).
[0019] Furthermore, in step S1, during the first heating and stirring, the reaction temperature is 30-80° C., and the stirring time is 0.5-3 h; during the second heating and stirring, the reaction temperature is 30-80° C., and the stirring time is 1-4 h.
[0020] Furthermore, in step S1, during the drying, the drying temperature is 80-150° C., and the drying time is 4-12 hours.
[0021] Furthermore, in step S1, the dried material is sieved to obtain a 10-60 mesh material, which is then roasted.
[0022] Furthermore, in step S2, the aluminum source is aluminum oxide, selected from one or more of aluminum nitrate, aluminum sulfate, aluminum isopropoxide or sodium aluminate. Preferably, the aluminum source is sodium aluminate.
[0023] Furthermore, in step S2, the silicon-aluminum ratio of the dendritic silicon source carrier to the aluminum source is 1:(5-30); in the impregnation, the impregnation temperature is 20-50°C, and the impregnation time is 10-30h; in the drying, the drying temperature is 80-150°C, and the drying time is 4-12h.
[0024] Furthermore, in step S2, during the drying, the drying temperature is 80-150° C., and the drying time is 4-12 hours.
[0025] Furthermore, in step S3, in the ammonia ion exchange, the ion exchanger used is selected from one or more of ammonium chloride, ammonium nitrate or ammonium sulfate. Preferably, the ion exchanger is ammonium chloride.
[0026] Furthermore, the mass ratio of the dendritic catalyst to the ion exchanger is (1-10):(50-100); in the hydrothermal reaction, the reaction temperature is 30-80° C. and the reaction time is 0.5-3 h.
[0027] Furthermore, in any one of steps S1, S2 or S3, in the calcination, the calcination temperature is 300-600°C, the calcination time is 1-6 hours, the calcination atmosphere is air, and the calcination apparatus is a muffle furnace or a tube furnace.
[0028] The second aspect of the present invention provides a hydrogen-type dendritic catalyst, which is prepared by the method provided by the first aspect.
[0029] The third aspect of the present invention provides an application of a hydrogen-type dendritic catalyst, wherein the catalyst is used for catalyzing the polymerization of α-olefins to prepare poly-α-olefins.
[0030] Further, the catalytic polymerization conditions include: temperature of 120°C to 210°C, pressure of 0.5 to 2.0 MPa, and a mass ratio of catalyst to raw material of 1:5 to 1:20. The reaction atmosphere includes a nitrogen atmosphere. The raw material includes decene. The reaction solvent includes heptane.
[0031] The preparation method of the present invention is economical and efficient, and the prepared catalyst has three-dimensional central radial channels and multi-level pore structure, higher specific surface area, larger pore volume, and easier contact of the inner surface of the particles, which is conducive to the diffusion of reactants and polymerization products, making it have better stability. In addition, in the process of preparing PAO by catalytic polymerization, the proportion of oligomers in the product can be adjusted by changing the silicon-aluminum ratio, thereby regulating the performance of PAO lubricating oil.
[0032] Compared with the prior art, the present invention has the following characteristics:
[0033] 1) The hydrogen-type dendritic catalyst prepared by the present invention not only has higher activity and selectivity in the polymerization process of α-olefins, but also has good stability; experiments show that when the reaction conditions are: temperature 120°C to 210°C, pressure 0.5 to 2.0 MPa, and catalyst to raw material ratio 1:5 to 1:20, the decene conversion rate is 5 to 90%, and the selectivity of the oligomerization product is 60 to 90%;
[0034] 2) The hydrogen-type dendritic catalyst prepared by the present invention can adjust the proportion of oligomers in the product by changing the silicon-aluminum ratio;
[0035] 3) The catalyst of the present invention has low preparation cost and simple reaction conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a flow chart for preparing a hydrogen-type dendritic catalyst;
[0037] Figure 2 is the XRD pattern of the hydrogen-type dendritic catalyst prepared in Example 1;
[0038] Figure 3 This is the SEM spectrum of the hydrogen-type dendritic catalyst prepared in Example 1;
[0039] Figure 4 is the NMR spectrum of the hydrogen-type dendritic catalyst prepared in Example 1;
[0040] Figure 5 This is the XPS spectrum of the hydrogen-type dendritic catalyst prepared in Example 1;
[0041] Figure 6 This is a gas phase mass spectrum of the product obtained when the hydrogen-type dendritic catalyst prepared in Example 1 is used to catalyze the polymerization of α-olefins; Figure 7 This is the gas chromatography-mass spectrometry analysis spectrum of the polymer product prepared in Example 1. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0043] Embodiment 1:
[0044] A hydrogen-type dendritic catalyst, the preparation method of which is as follows Figure 1 As shown, the following steps are included:
[0045] S1: Preparation of dendritic silicon source support
[0046] S1-1: Weigh 4.1 g of triethanolamine (alkali source) and dissolve it in 1500 g of deionized water. Heat to 80° C. and stir to react for 0.5 h to obtain an alkali source solution.
[0047] S1-2: Keeping the temperature constant, continue to add 10.1 g of sodium salicylate (structure regulator) and 22.8 g of hexadecyltrimethylammonium bromide (surfactant) to the alkaline source solution in step S1-1, and stir the reaction for 1 hour to obtain a mixed solution.
[0048] S1-3: Keep the temperature constant, and then add 224.3 g of tetraethyl orthosilicate (silicon source) dropwise to the mixed solution of step S1-2, adjust the speed to 300 rpm, stir and react for 2 hours, and cool to obtain a milky white slurry.
[0049] S1-4: The milky white slurry of step S1-3 was centrifuged, the supernatant was removed, washed and dried at 80°C for 12h. The slurry was ground and sieved to obtain a 10-20 mesh carrier, which was calcined at 550°C in air for 6h to obtain a dendritic silicon source carrier (average pore size 11.80nm, specific surface area 477.52m 2 / g, pore volume 1.93cm 3 / g).
[0050] S2: Preparation of dendritic catalyst (incorporation of aluminum source)
[0051] 2.73 g NaAlO2 (aluminum source) was dissolved in 1000 g deionized water, 10 g of the dendritic silicon source carrier prepared above was added, and the mixture was immersed at 30° C. for 24 h, cooled, centrifuged, washed, dried at 80° C. for 12 h, and then calcined at 550° C. for 6 h in an air atmosphere to obtain a dendritic catalyst.
[0052] S3: Preparation of hydrogen-type dendritic catalyst (ion exchange)
[0053] S3-1: Add 1000 g of deionized water to a well-sealed reactor, add 53.49 g of ammonium chloride (ion exchanger) under stirring, add 10 g of dendritic catalyst after dissolution, heat to 80° C., stir and react for 0.3 h to obtain a mixed solution.
[0054] S3-2: The mixed solution in step S3-1 is cooled, centrifuged, washed, dried at 80° C. for 12 h, and then calcined at 550° C. for 6 h in an air atmosphere to obtain a hydrogen-type dendritic catalyst.
[0055] The analysis results of the hydrogen-type dendritic catalyst prepared in Example 1 are as follows:
[0056] from Figure 2 (XRD) shows that the catalyst has an obvious broad peak at 2θ=23°, which is attributed to the characteristic peak of amorphous silica. This shows that the pores of silica in the catalyst are orderly, with high crystallinity and no other impurities.
[0057] from Figure 3 It can be seen from the SEM that the catalyst particle size is highly uniform, the surface presents a wrinkled morphology, and the overall structure is a central radial dendritic network structure, showing a three-dimensional spherical shape, and the pores are separated by dense layers, forming a uniform three-dimensional mesoporous network. The edges of the dendritic structure are clear, without obvious cracks or defects. The surface of the three-dimensional sphere is not smooth, which is due to the fact that the incorporation of aluminum will cause some changes in the morphology of the sample.
[0058] from Figure 4 It can be seen from (NMR) that chemical shifts occur at δ = 55ppm and δ = 0ppm. The chemical shift at δ = 55ppm indicates that Al species are successfully introduced into the skeleton of the sample carrier, forming a tetracoordinated skeleton aluminum; while the resonance peak at the chemical shift of 0ppm belongs to the hexacoordinated aluminum free from the skeleton. Usually, the hexacoordinated aluminum free from the skeleton mainly forms Lewis acid sites, and the tetracoordinated aluminum on the skeleton mainly forms Acid position.
[0059] XPS was used to study the surface element composition and atomic valence information of hydrogen-type dendritic catalysts. Figure 5 It can be seen from the XPS that the XPS total spectrum includes C1s, O 1s, Si 2p and Al 2p signals. Among them, the C1s peak at 297.9eV comes from the hydrocarbon peak in the XPS instrument. The Si 2p signal at 103.4eV indicates that silicon is present in the sample as [SiO4] 4-The unit is connected to oxygen. Similarly, the strong signal in the 532.8eV region belongs to the O1s signal, which corresponds to the Si-O bond from the silica skeleton. In addition, the peak at 75.15eV in the figure is the Al signal, which corresponds to a chemical state different from the Al2O3 form, further illustrating the introduction of aluminum species.
[0060] Application of Catalytic α-Olefin Oligomerization
[0061] 100 g of the raw material 1-decene, 100 g of the solvent 1-heptane, and 10 g of the hydrogen-type dendritic catalyst were added to a stirred reactor, which was sealed and ventilated with nitrogen for 15 min. The reaction temperature of the reactor was set to 180° C., the reaction time was 8 h, and the reaction pressure was 1 MPa. The polymerization reaction was carried out. The product was filtered and then analyzed by gas chromatography. The analysis results are as follows: Figure 6 And as shown in Table 2.
[0062] from Figure 6 From the GC-MS spectrum, it can be seen that the peak appearing at around 3.6 min is the solvent heptane, which is not included in the reaction results. Decene, decane and their isomers appear at around 8.5-11.5 min. The dimer, i.e. decene dimer and its isomers, appears at around 27.6 min, and the trimer, i.e. decene trimer and its isomers, appears at around 32.4 min. Among them, dimers and trimers are the target products, and the rest are impurities formed by the side reactions of decene under acid catalysis. The GC-MS analysis spectrum of the polymerization product is shown below: Figure 7 shown.
[0063] Example 2-22:
[0064] A hydrogen-type dendritic catalyst, the preparation method of which is different from that of Example 1 only in that:
[0065] The types and / or amounts of the structure regulator, surfactant, alkali source, silicon source, and aluminum source are different, as shown in Table 1. The remaining conditions, including those not specifically mentioned in Table 1, are the same as those in Example 1.
[0066] Catalyze the polymerization of α-olefins. The reaction conditions are different from those in Example 1 only in that:
[0067] The reaction temperature and reaction time are different, as shown in Table 1. The other olefin polymerization conditions not specifically mentioned are the same as those in Example 1.
[0068] Table 1 Detailed explanation of the embodiment
[0069]
[0070]
[0071] Comparative Example 1:
[0072] A catalyst, the preparation method of which comprises the following steps:
[0073] Preparation of carrier: Take 10-20 mesh one-dimensional pore material MCM-41 (average pore size 2.11nm, specific surface area 577m 2 / g, pore volume 0.6cm 3 / g), and calcined at 550℃ for 6h to obtain a dendritic carrier.
[0074] Aluminum source incorporation: 2.73 g NaAlO2 (aluminum source) was dissolved in 1000 g deionized water, 10 g of the dendritic support was added, and the mixture was immersed at 30°C for 24 h, cooled, centrifuged, washed, dried at 80°C for 12 h, and then calcined at 550°C for 6 h to obtain a heterogeneous catalyst.
[0075] Ion exchange: Add 1000g of deionized water to a well-sealed reactor, add 53.49g of ammonium chloride under stirring, add 10g of the pre-prepared heterogeneous catalyst after dissolving, heat to 80°C, stir and react for 0.3h. Cool, centrifuge, wash, dry at 80°C for 12h, and calcine at 550°C for 6h. A hydrogen-type one-dimensional channel catalyst is obtained.
[0076] Using 1-decene as raw material, polymerization was carried out under the same conditions as in Example 1. Some properties of the synthesized PAO are shown in Table 6.
[0077] Comparative Example 2:
[0078] A catalyst, the preparation method of which is different from that of Comparative Example 1 in that:
[0079] The carrier in Comparative Example 1 was replaced with a two-dimensional hexagonal through-pore material SBA-15 (average pore size 7.5 nm, specific surface area 700 m 2 / g, pore volume 0.81cm 3 The remaining materials and methods are the same as those in Example 1.
[0080] Using 1-decene as raw material, polymerization was carried out under the same conditions as in Example 1. Some properties of the synthesized PAO are shown in Table 6.
[0081] Comparative Example 3:
[0082] A catalyst, the preparation method of which is different from that of Example 1 in that:
[0083] The surfactant used in preparing the carrier in Example 1 was removed, and the remaining materials and steps were the same as in Example 1.
[0084] Using 1-decene as raw material, polymerization was carried out under the same conditions as in Example 1. Some properties of the synthesized PAO are shown in Table 6.
[0085] Comparative Example 4
[0086] A catalyst, the preparation method of which is different from that of Example 1 in that:
[0087] The structure regulator used in preparing the carrier in Example 1 was removed, and the remaining materials and steps were the same as in Example 1.
[0088] Using 1-decene as raw material, polymerization was carried out under the same conditions as in Example 1. Some properties of the synthesized PAO are shown in Table 6.
[0089] Calculation method (normalized calculation, and the solvent ratio is removed):
[0090]
[0091] Target product selectivity = dimer selectivity + trimer selectivity
[0092]
[0093] The polymerization reaction results of the above examples and comparative examples are shown in Tables 2-6.
[0094] Table 2 Comparison of the effects of synthesizing embodiments using different raw material ratios
[0095]
[0096] Table 3 Comparison of the effects of the synthetic examples using different reaction conditions (temperature, time)
[0097]
[0098]
[0099] Table 4 Comparison of the effects of synthesizing examples using different alkaline sources, surfactants, and structure regulators
[0100]
[0101] Table 5 Comparison of the effects of synthesizing embodiments using different aluminum sources and silicon sources
[0102]
[0103] Table 6 Comparison of the effects of using different carriers on the synthesis examples
[0104]
[0105]
[0106] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a hydrogen-type dendritic catalyst, characterized in that: The following steps are involved: S1: heating and stirring the alkali source, surfactant and structure regulator, and then adding the silicon source for secondary heating and stirring, cooling to obtain a milky white slurry, drying and calcining to obtain a dendritic silicon source carrier; S2: mixing the dendritic silicon source carrier and the aluminum source, impregnating, drying and calcining to obtain a dendritic catalyst; S3: exchanging the dendritic catalyst with ammonia ions and calcining the catalyst to obtain a hydrogen-type dendritic catalyst.
2. The method for preparing a hydrogen-type dendritic catalyst according to claim 1, characterized in that: In step S1, the alkali source is selected from one or more of triethanolamine, ethylenediamine or ammonium hydroxide; the surfactant is selected from one or more of hexadecyltrimethylammonium chloride, hexadecyldimethylammonium chloride or hexadecyltrimethylammonium bromide; the structure regulator is selected from one or more of sodium salicylate, sodium laurate or sodium dodecyl sulfate; the silicon source is selected from one or more of sodium silicate, tetramethyl orthosilicate, tetraethyl orthosilicate or silica sol.
3. The method for preparing a hydrogen-type dendritic catalyst according to claim 1, characterized in that: In step S1, the mass ratio of the alkali source, surfactant, structure regulator and silicon source is (3-5):(20-24):(9-12):(220-225).
4. The method for preparing a hydrogen-type dendritic catalyst according to claim 1, characterized in that: In step S1, during the first heating and stirring, the reaction temperature is 30-80°C, and the stirring time is 0.5-3h; during the second heating and stirring, the reaction temperature is 30-80°C, and the stirring time is 1-4h.
5. The method for preparing a hydrogen-type dendritic catalyst according to claim 1, characterized in that: The aluminum source is selected from one or more of aluminum nitrate, aluminum sulfate, aluminum isopropoxide or sodium metaaluminate.
6. The method for preparing a hydrogen-type dendritic catalyst according to claim 1, characterized in that: In step S2, the silicon-aluminum ratio of the dendritic silicon source carrier to the aluminum source is 1:(5-30); in the impregnation, the impregnation temperature is 20-50°C and the impregnation time is 10-30h; in the drying, the drying temperature is 80-150°C and the drying time is 4-12h.
7. The method for preparing a hydrogen-type dendritic catalyst according to claim 1, characterized in that: In step S3, in the ammonia ion exchange, the ion exchanger used is selected from one or more of ammonium chloride, ammonium nitrate or ammonium sulfate; the mass ratio of the dendritic catalyst to the ion exchanger is (1-10):(50-100); in the hydrothermal reaction, the reaction temperature is 30-80° C. and the reaction time is 0.5-3 h.
8. The method for preparing a hydrogen-type dendritic catalyst according to claim 1, characterized in that: In any one of steps S1, S2 or S3, in the calcination, the calcination temperature is 300-600° C. and the calcination time is 1-6 hours.
9. A hydrogen-type dendritic catalyst, characterized in that The method is prepared by any one of claims 1 to 8.
10. A use of the hydrogen-type dendritic catalyst as claimed in claim 9, characterized in that: The hydrogen-type dendritic catalyst is used for catalyzing the polymerization of alpha-olefins to prepare poly-alpha-olefins.
Citation Information
Patent Citations
Method for producing catalyst component for olefin polymerization, method for producing catalyst for olefin polymerization, and method for producing olefin polymer
JP2018087285A
Olefin polymerization metallocene catalyst composition, preparation thereof and use thereof
WO2023246009A1
